How to Capture the Bleeding Phenotype in FXI-Deficient Patients - Bertaggia Calderara, Debora; Zermatten, Maxime G.; Aliotta, Alessandro; Alberio, Lorenzo (Hämostaseologie, 2020)
Factor XI (FXI) is a serine protease involved in the propagation phase of coagulation and in providing clot stability. Several mutations in the F11 gene lead to FXI deficiency, a rare mild bleeding disorder. Current laboratory methods are unable to assess bleeding risk in FXI-deficient patients, because the degree of bleeding tendency does not correlate with plasma FXI activity as measured by routine coagulometric aPTT–based assays. Bleeding manifestations are highly variable among FXI-deficient patients and FXI replacement therapy can be associated with an increased thrombotic risk. A correct evaluation of the patient hemostatic potential is crucial to prevent under- or overtreatment. In recent years, different research groups have investigated the use of global coagulation assays as alternative for studying the role of FXI in hemostasis and identifying the clinical phenotype of FXI deficiency. This brief review article summarizes the main features of coagulation factor XI and its deficiency and resumes the principle axes of research and methods used to investigate FXI functions.
Keywords: coagulation factor XI; FXI deficiency; global assays; thrombin generation; hemostatic potential